2014
DOI: 10.2147/cpaa.s36600
|View full text |Cite
|
Sign up to set email alerts
|

Melatonergic drugs in development

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is widely known as “the darkness hormone”. It is a major chronobiological regulator involved in circadian phasing and sleep-wake cycle in humans. Numerous other functions, including cyto/neuroprotection, immune modulation, and energy metabolism have been ascribed to melatonin. A variety of studies have revealed a role for melatonin and its receptors in different pathophysiological conditions. However, the suitability of melatonin as a drug is limited because of its shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 115 publications
(124 reference statements)
0
30
0
2
Order By: Relevance
“…Based on the on evidence-based treatment of insomnia, parasomnia, and circadian rhythm sleep disorders, the British Association for Psychopharmacology concluded that melatonin is the first-choice treatment when a hypnotic is indicated in patients aged more than 55 years. 1,11,12,[14][15][16] A recent post-marketing surveillance study conducted by Hajak et al, 17 also proved the efficacy of the prolonged-release melatonin, circadin.…”
Section: Melatonin -Pharmacological and Clinical Rolementioning
confidence: 96%
See 2 more Smart Citations
“…Based on the on evidence-based treatment of insomnia, parasomnia, and circadian rhythm sleep disorders, the British Association for Psychopharmacology concluded that melatonin is the first-choice treatment when a hypnotic is indicated in patients aged more than 55 years. 1,11,12,[14][15][16] A recent post-marketing surveillance study conducted by Hajak et al, 17 also proved the efficacy of the prolonged-release melatonin, circadin.…”
Section: Melatonin -Pharmacological and Clinical Rolementioning
confidence: 96%
“…The gene coding for AANAT is directly influenced by the photoperiod and also the mRNAs encoding for these enzymes involved in the synthetic pathway of melatonin are expressed with a day/night rhythm. 1,6,7 As discussed above melatonin biosynthesis is synchronized to the light/dark cycle by the suprachiasmatic nucleus (SCN). SCN, the internal "biological clock," gets photic input from the external environment via the retinohypothalamic tract.…”
Section: Pathophysiological Functions Of Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…Readily passing through the blood brain barrier, melatonin increases daytime sleep duration with little effect on sleep latency for night-shift workers (Sharkey et al 2001;Liira et al 2015) and phase-shifts circadian rhythms in simulated night-shift studies . During the day, the circadian system maintains arousal in the face of increased time awake with decreased arousal at night due, in part, to rising melatonin levels which target MT 1 and MT 2 receptors in the SCN to dampen SCN driven arousal signals (Dodson and Zee 2010;Carocci et al 2014). Melatonin is used as a treatment of circadian perturbations including jet lag, shift work, or delayed sleep disorder (PandiPerumal et al 2008;Brown et al 2009;Srinivasan et al 2010) and can be used in combination with bright light therapy, to accelerate reentrainment for jet lag (Dodson and Zee 2010;Zee and Goldstein 2010).…”
Section: Countermeasures For Circadian Desynchronymentioning
confidence: 99%
“…Melatonin is used as a treatment of circadian perturbations including jet lag, shift work, or delayed sleep disorder (PandiPerumal et al 2008;Brown et al 2009;Srinivasan et al 2010) and can be used in combination with bright light therapy, to accelerate reentrainment for jet lag (Dodson and Zee 2010;Zee and Goldstein 2010). Newly developed selective MT 1 /MT 2 receptor agonists (Srinivasan et al 2010;Carocci et al 2014) include Ramelteon which effectively acts as a phase shifting agent in humans (Richardson et al 2008;Carocci et al 2014) and animal models (Rawashdeh et al 2011) as well as Tasimelteon which facilitates entrainment to a 24-h cycle maintaining melatonin rhythms, sleep latency, and sleep quality (Carocci et al 2014;Neubauer 2015). (4) The use of wakefulness promoting drugs to increase arousal and performance in circadian disorders include caffeine and modafinil.…”
Section: Countermeasures For Circadian Desynchronymentioning
confidence: 99%